Una visión actual del CIAEM: primeros años del siglo XXI - Sánchez Fernández, Carlos (2019)
What has been the evolution of the Inter-American Committee on Mathematical Education (IACME) in the 21st century? What are its main goals and accomplishments? What has been its relationship with the international community of Mathematics Education, and, in particular, with the International Commission on Mathematical Instruction (ICMI)? How has  it participated in the creation and strengthening of new regional spaces for Mathematics Education? And beyond the organizational dimensions: What have been the dominant themes in the plenary activities of the Inter-American Mathematics Education Conferences? From these basic questions, we will try to channel a prudent, pluralistic and critical reflection on the most recent past of IACME. In these few years lived in the 21st century - specifically from the XI Conference (2003, Blumenau) - there has been a positioning of IACME beginning with the cultivation of academic quality, an undeniable closer connection with the international community, uses of technologies, and dynamics and characteristics that allow us to affirm that there has been a qualitative leap in the history of this group. Our purpose is to stimulate conscious reflection, extract fertile ideas and suggest effective actions that maintain a high level of social services in the Americas.